Methods and Simulations used to Detect Photons from Exoplanets of a Parent Star - Talib, Ali; Onofrio, A. D’; Terrasi , F. (Iraqi Journal of Science, 2022)
The extrasolar planets in the vicinity of stars are expected to be bright enoughand are very difficult to be observed by direct detection. The problem is attributed tothe side loops of the star that created due to the telescope diffraction processing.Several methods have been suggested in the literatures are being capable to detectexoplanet at a separation angle of 4λ/D and at a contrast ratio of 10-10. Thesemethods are more than one parameter function and imposing limitations on the innerworking distance. New simple method based on a circular aperture combined with athird power Gaussian function is suggested. The parameters of this function are thenoptimized based on obtaining a minimum inner working distance This method iscapable of detecting exoplanet with an angular separation of 4λ/D and a contrastratio of 10-10 and it is much easier to be implemented practically.